Implementasi Metode SMART Pada Sistem Pendukung Keputusan Dalam Seleksi Penerimaan Beasiswa Di SMA Negeri 6 Tangerang Selatan - Chika Permata Putri; Fitri Yanti (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
In each period of the new school year, the student division selects students and students who have registered as scholarship recipients. At SMAN 6 South Tangerang, a computerized method has not been applied to help select scholarship recipients, and the selection process is still done manually so that it is still less effective and less efficient. The method that will be used in making this decision support system is the Simple Multi Attribute Rating Technique (SMART) method. The SMART method was chosen to solve problems in the selection of scholarship recipients because this method is able to provide the best alternative by giving weight to each criterion that describes how important these criteria are with other criteria. Based on the results of testing with blackbox and whitebox test cases, it can be concluded that the development of a decision support system in the selection of scholarship recipients using the SMART method is successful. There were no process errors and functionally managed to produce the expected results. This system was successfully built in a computerized manner to speed up the selection process and provide effective and efficient recommendation results.